2015
DOI: 10.1186/s13012-015-0347-5
|View full text |Cite
|
Sign up to set email alerts
|

What is the effectiveness of printed educational materials on primary care physician knowledge, behaviour, and patient outcomes: a systematic review and meta-analyses

Abstract: BackgroundPrinted educational materials (PEMs) are commonly used simple interventions that can be used alone or with other interventions to disseminate clinical evidence. They have been shown to have a small effect on health professional behaviour. However, we do not know whether they are effective in primary care. We investigated whether PEMs improve primary care physician (PCP) knowledge, behaviour, and patient outcomes.MethodsWe conducted a systematic review of PEMs developed for PCPs. Electronic databases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 49 publications
2
46
0
9
Order By: Relevance
“…[44][45][46] With respect to quality improvement in a complex setting, the literature suggests that distribution of new guidelines will not be sufficient to improve care delivery. 47 In successful implementation, two mutually reinforcing, evidence-based [48][49][50][51] and theory-informed 52,53 implementation strategies are needed: (i) office policies that fit the practice, patients and local conditions such as a protocol on evidence-based practice guidelines, with algorithms and checklists; and (ii) office practices such as feedback on audit with performance goals. Dental teams supported by their supervisors should create goals for care delivery, and performance should be monitored frequently to meet goals.…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46] With respect to quality improvement in a complex setting, the literature suggests that distribution of new guidelines will not be sufficient to improve care delivery. 47 In successful implementation, two mutually reinforcing, evidence-based [48][49][50][51] and theory-informed 52,53 implementation strategies are needed: (i) office policies that fit the practice, patients and local conditions such as a protocol on evidence-based practice guidelines, with algorithms and checklists; and (ii) office practices such as feedback on audit with performance goals. Dental teams supported by their supervisors should create goals for care delivery, and performance should be monitored frequently to meet goals.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the peak organisations advocate for multifaceted interventions when implementing guidelines. 1 Commonly recommended interventions by these organisations are: educational sessions [17], academic detailing [18][19][20], continuing medical education (CME) [21][22], provision of printed educational material [23], use of opinion leaders to endorse guidelines [24], and engaging target populations who will use the guideline [25]. However, the magnitude of effect from Abbreviations: CME, continuing medical education; FMC, Flinders Medical Center; GIN, Guideline International Network; ICCU, Intensive and critical care unit; IOM, Institute of Medicine; JMO, junior medical officer; MRSA, methicillin-resistant Staphylococcus aureus; NHMRC, National Health and Medical Council; NICE, National Institute for Clinical Excellence, SIGN, Scottish Intercollegiate Guideline Network; VRE, vancomycin-resistant Enterococcus.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we found that for 78% of products with aRMMs for ME safety concerns, studies were in place to measure the effectiveness of these measures. The effectiveness of educational materials is debated and the materials may not always have the intended effect [23]. Effectiveness studies are important to decide whether RMMs are adequate or should be amended, although the execution often remains a challenge [24][25][26].…”
Section: Discussionmentioning
confidence: 99%